Ameliorative Effect of Adjunct Therapy of Metformin with Atorvastatin on Streptozotocin-induced Diabetes Mellitus in Rats - Singh, B. K.; Singh, A.; Kumar, V. (Drug Research, 2016)
Metformin has been used for the treatment of diabetes, whereas atorvastatin reduces the incidence of atherosclerosis and ischemic heart disease. Therefore, combined treatment with meformin plus atorvastatin may be beneficial in diabetic patients associated with cardiac disease. The present study was designed to evaluate the combination therapy of metformin and atorvastatin on streptozotocin-induced diabetes mellitus in rats. Blood pressure, serum insulin, glucose, lipid profiles and antioxidant enzymes in pancreatic tissues were measured. Histopathological examination of pancreatic tissues was performed. Streptozotocin treated rats showed significant decrease in body weight and body mass index. Streptozotocin-treated rats showed a significant increase in the levels of blood pressure, serum glucose, triglycerides, total cholesterol and thiobarbituric acid reactive substance as well as a significant decrease in the levels of serum insulin, high density lipoprotein and reduced glutathione in pancreatic tissues. Administration of metformin plus atorvastatin for a period of 14 days significantly improved these biochemical parameters near to normal. The protective effect of metformin plus atorvaststin against streptozotocin-induced diabetes was further confirmed by histopathological examination. The results of present study suggest that metformin plus atorvastatin possess antioxidant activity and has a significant protective effect against streptozotocin-induced diabetes mellitus.
Keywords: diabetes mellitus; metformin; atorvastatin; lipid profiles; oxidative stress